2021
DOI: 10.1101/2021.07.02.21259897
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anti-spike antibody response to natural SARS-CoV-2 infection in the general population

Abstract: We estimated the duration and determinants of antibody response after SARS-CoV-2 infection in the general population using representative data from 7,256 United Kingdom COVID-19 infection survey participants who had positive swab SARS-CoV-2 PCR tests from 26-April-2020 to 14-June-2021. A latent class model classified 24% of participants as 'non-responders' not developing anti-spike antibodies. These seronegative non-responders were older, had higher SARS-CoV-2 cycle threshold values during infection (i.e. lowe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
44
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 49 publications
7
44
0
1
Order By: Relevance
“…We found that females had a higher peak IgG level for both vaccines and a longer half-life for BNT162b2, similarly to natural infection 16 , and consistent widely reported enhanced immune responses in females 24–28 . Healthcare workers had higher IgG peak levels for both vaccines, potentially reflecting a “healthy worker” effect 29 , ongoing occupational exposure or undetected prior infection.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…We found that females had a higher peak IgG level for both vaccines and a longer half-life for BNT162b2, similarly to natural infection 16 , and consistent widely reported enhanced immune responses in females 24–28 . Healthcare workers had higher IgG peak levels for both vaccines, potentially reflecting a “healthy worker” effect 29 , ongoing occupational exposure or undetected prior infection.…”
Section: Discussionsupporting
confidence: 87%
“…Comparing the effects of factors between the two vaccines, and with our previous findings on natural infection 16 (Figure 5) , effects of some factors were relatively consistent between ChAdOx1, BNT162b2 and/or natural infection, albeit with differing effect sizes (e.g age, sex, on half-life; sex, ethnicity on peak; prior infection on peak and half-life), whilst for others effects were in opposite directions (e.g age on peak, ethnicity on half-life). As above, other than for prior infection, factors had a much greater effect for BNT162b2 than ChAdOx1, particularly on half-life.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…≥ 1.1) as having been infected by the SARS-CoV-2. This choice may tend to underestimate the number of subjects who have been infected with the COVID 19 virus as (i) indeterminate results (between 0.8 and 1.1) were considered as negative, (ii) there is evidence that the humoral immunity developed in the weeks following infection decreases over time (though this issue was partly controlled as DBS were mostly collected soon after the first epidemic wave) [28] and (iii) 10% to 20% of infected individuals will not mount a detectable humoral response [29,30]. Thus, though this case definition favoured specificity over sensitivity and limits the occurrence of false positive cases, we may have selected infected participants whose initial humoral response was intense while infected participants with a milder immune response may have not been detected.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, other SARS-CoV-2 infected individuals may also experience a variety of disease-related complications including liver injury (Saviano et al, 2021), kidney injury (Han and Ye, 2021), and cardiovascular complications including myocarditis, heart failure, thrombosis (Long et al, 2020), and thrombocytopenia (Mei et al, 2020). COVID-19 can trigger a range of antibody response levels (Wei et al, 2021) and an enrichment in autoantibodies that react with human proteins has been found for patients with severe disease (Wang et al, 2021). While the reason for the variety of disease severity affecting people with COVID-19 is not well understood, molecular mimicry may provide an avenue for explanations.…”
Section: Introductionmentioning
confidence: 99%